Updated Images of Damage to Differentiate Between Spouses - Ban Badr Hassan (Journal of Legal Sciences, 2024)
The Iraqi legislation, in its desire to protect the parties to the marital bond, allowed each of the spouses to file a separation claim for damage, and the cases of damage mentioned in Article (40) of the Iraqi Personal Status Law were cited as examples, which means the creation of cases within the meaning of damage, the practical reality indicates the existence of new cases that are requires the separation of harm, including the wrong use of spouses for social exchange networks, and what is due to the violence exerted by one spouse to the other and the so-called ( family violence). The reason for the separation may be due to the deviant ideas that have plagued Arab societies as well as biological, psychological and social motives that led to the desire of one spouse to change his gender, which causes harm to the other spouse.